Effects of osteoporosis educational prevention program to promote calcium intake and exercise among female university students in Iran - Jamshidian-Tehrani, Maryam (2012)
Osteoporosis is known as a silent disease as it is often not diagnosed until an individual presents with a low impact fracture. Many people of all ages appear to be unaware of the risk factors and preventive behaviors associated with osteoporosis. Adolescence and young adulthood is a period of significant growth and change. During this time the majority of bone mass is accumulated. Education to increase awareness of risk factors and preventive behaviors is identified as being paramount in helping to prevent the onset of this disease later in life. Therefore, a randomized controlled trial was designed to investigate the effect of a three-month osteoporosis educational prevention program based on the Health Belief Model (HBM), on osteoporosis knowledge, health beliefs, self-efficacy and behaviors such as calcium intake and exercise toward osteoporosis prevention among young female university students in Iran. A sample of 128 new in-coming female students, who met the inclusion and exclusion criteria, participated in the study. They were randomly assigned to the intervention (n=61) and control group (n=67). Participants in the intervention group were exposed to a three-month multi-component intervention program comprised of six structured modules including educational lecture, self study materials (a series of pamphlets and booklets,), individual face-to-face consultation, emails and phone call reminders. The total contact time for the entire program was about eight hours. The control group did not receive any information during the study time. The instruments of study were HBM questionnaires, including Osteoporosis Knowledge Test (OKT), Osteoporosis Health Belief Scale (OHBS) and Osteoporosis Self-efficacy Scale (OSES), semi-food frequency and exercise questionnaires. OKT was assessed at baseline, immediately after the lecture and three months follow-up intervention and was analyzed through Analysis of Covariance (ANCOVA) with repeated measures (for controlling difference in OKT risk factor at baseline between the two groups). The OHBS, OSES, calcium intake, and exercise habits were assessed at baseline and three months post- intervention. The results showed that the participants in the intervention group significantly (p<0.001) increased their scores in OKT (45.1%), OHBS (26.8%) and OSES (8.9%) compared with the control group (OKT=12.1%, OHBS=0.8% and OSES=1.9%). The results also revealed a significant (p<0.001) increase (36.7%) in calcium intake in the intervention group compared with the control group (2.1%) after three months follow-up intervention. Similarly, the intervention group had significantly higher number of time per/week (p<0.001), and total duration minutes per/week (p<0.017) of weight-bearing exercise compared to the control group. In conclusion, a three-month multi-component educational intervention program using HBM was effective to improve osteoporosis knowledge, change health beliefs about osteoporosis and increase self-efficacy in adopting preventive behaviors among Iranian young female adults. Therefore, this approach should be widely used at the university setting to promote the adoption of osteoporosis prevention behaviors including intake of calcium-rich foods and regular weight-bearing exercise among young adults. In future studies, other strategies and approaches to promote preventive behaviors should also be explored. Future studies should also include a larger representative sample and should evaluate the longer-term effects of the educational intervention.